Inhibition growth of Aspergillus niger that isolated from some fodder grains by using the Pleurotus ostreatus and Calcium citrate - Mohammed Al-mohaidi; Abdul_ameer S. Saadon (Al-Qadisiyah Journal of Pure Science, 2020)
Samples were collected from the stores , fields and local markets of Diwaniya province for the purpose of study  from August / October 2019, the following fungi were isolated: Aspergillus niger, Aspergillus flavus, Aspergillus ochraceus, Aspergillus fumigatus, Penicillium natatum , Rhizopus stolanifer, Alternaria Alternata, Fusarium solani, Fusarium proliferatum, Fusarium sp. Tricoderma sp. . Some significant differences were observed in the frequency of fungi isolated from fodder grains , the  frequency percentage highest in the treatment of non-sterilized grains reach 15.23% for the A. niger fungus and in sterilized grain about 13.88% . A.niger diagnosed phenotypic using classification keys and molecular diagnosed with PCR technique (polymerase chain reaction) with sequencing analysis and phylogenic tree analysis for the purpose of comparing A.niger fungi isolates with some global strains . The effect of  p.ostreatus showed ability of this fungus to inhibit growth of A.niger fungus when the antagonism occur between two fungus  . Interference between p.ostreatus filtrate concentration  and calcium citrate effect in the radial growth of the this fungus showed a clear decrease in the level of colonial diameters , where the inhibition percent reached to 71.79±0.06% at concentration 30% .